Studi Tafsir dalam Akademia Barat: - Muchlisin, Annas Rolli (SUHUF, 2022)
This paper observes how the field of tafsir studies has continued to establish itself as an important discipline within Islamic studies in Western academia. It traces how the previous scholarship, which was more preoccupied with Qur’anic studies, has shifted attention to Qur’an commentaries rather than exclusively to the Qur’anic text. Although not an exhaustive survey of all Western works devoted to tafsir literature as it excludes studies on modern tafsir, this paper confirms the significance of the classical and, more importantly, medieval tafsir tradition as a lens through which Islamic intellectual history can be approached. By surveying bibliographical data produced in the past few decades, this article has found that Sunni and mystical Qur’an commentaries have received greater scholarly investigation, that tafsir historians’ works have transformed traditional views on the history of tafsir, and that although the field of tafsir studies is still intimately connected with Qur’anic studies, some current publications testify that it might become an independent study.